Optimasi Formula dan Upaya Penutup Rasa (Taste Masking) Sediaan Orally Dissolving Film (ODF) Ekstrak Daun Sirih Hijau (Piper Betle L.) Sebagai Penyegar Mulut - Nugraheni, Firdha; Setiyadi, Gunawan (Journal of Pharmaceutical and Sciences, 2025)
Halitosis is caused mainly by bacterial decay and the generation of volatile sulfur compounds. Halitosis has oral causes, such as poor oral hygiene, periodontal disease, tongue coat, food impaction, dentures, damaged restorations, oral carcinoma, and throat infections. Green betel leaves are beneficial for oral health. Betel leaves contain flavonoid compounds, polyphenols, tannins and essential oils. Betel leaves contain essential oils of 1 – 4.2%, phenol compounds and kavikol. Kavikol has activity as a bactericide five times stronger than phenol. This extract can potentially be used as an active ingredient component in orally dissolving film (ODF) preparations. The purpose of this study was to determine the optimal concentration value of HPMC as a polymer and propylene glycol as a plasticizer based on physical properties such as pH, weight uniformity, film thickness, dissolving time and taste masking test of orally dissolving film (ODF) preparations of green betel leaf extract (Piper betle l.). The method used was Simplex Lattice Design (SLD) with a composition of 2% HPMC and 5% propylene glycol. The response results from the pH and dissolution time experiments with an average standard deviation, respectively, ranged from 6.67±0.020-6.73±0.026; 122.21±0.33 -122.85±0.29 mg; 0.2±0.005 mm - 0.21±0.01 mm, and 20.5±0.06 - 30.1±0.05 seconds. In taste masking, it has a fairly good ability to cover the bitter taste of green betel leaf extract.